HUBUNGAN ANTARA KOHESIVITAS KELOMPOK DAN SELF EFFICACY TERHADAP SOCIAL LOAFING PADA SISWA DI SMK NEGERI 11 SEMARANG - As’sidqi Aenudin Ms Hilmi; Lucy Hariadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2024)
This study aims to analyse the relationship between group cohesion (X1) and self- efficacy (X2) on social loafing (Y) in students at SMKN 11 Semarang. The number of samples used in this study were 226 class X students majoring in DKV and Animation at SMK N 11 Semarang. The sampling technique used in this research is incidental sampling technique. This research instrument uses social loafing scale based on Myers' theory, group cohesion scale basedon Forsyth's theory, and self-efficacy scale based on Bandura's theory. The data analysis technique used is Spearman's rho correlation. The results of this study indicate that cohesiveness and self-efficacy have a role in the occurrence of social loafing, this is evidenced by the significance value of .000 (p <0.05) indicating that there is a significant and negative relationship between group cohesiveness and self-efficacy on social loafing. The relationship between variables X and Y is evidenced by the obtained value = 0.000 (p < 0.05) and acorrelation value of -0.497 between group cohesiveness (X1) and social loafing and between self- efficacy and social loafing has a value = 0.000 (p < 0.05) and a correlation value of -0.413. Keywords: Social Loafing,Group Cohesion,Self efficacy